Evaluation the relationship between serum progesterone level and pain perception after cesarean delivery. (2nd November 2019) - Kashanian, Maryam; Dadkhah, Farideh; Zarei, Soghra; Sheikhansari, Narges; Javanmanesh, Forough
Abstract: Introduction: Cesarean delivery is the most common surgery in obstetrics, and pain relief after cesarean section is an important concern for obstetricians and their patients. Objective: The aim of this study was to evaluate the relationship between serum progesterone level and pain perception after cesarean delivery. Method: The study was performed as a prospective cohort study on 166 pregnant women who were candidates for elective cesarean delivery due to previous cesarean section. Before surgery, serum progesterone level was measured. Pain score of women was evaluated 4, 8, 12, and 24 h after surgery using visual analog scale (VAS) score, and correlation between progesterone level and pain was evaluated. Results: The median value of serum progesterone was 119.45 ng/ml. Mean pain score in hours 4, 8, 12, and 24 were 6.80 ± 2.11, 5.31 ± 1.48, 3.89 ± 1.68, and 2.30 ± 1.26, respectively. The women were divided according to mean progesterone level of 119.45 ng/ml into two groups of high progesterone level (≥119.45) and low progesterone level (<119.45), and the pain score was evaluated in different times (hour 4, 8, 12, and 24) for both levels of progesterone. The mean pain score in the 4, 8, 12, and 24 h were significantly lower in high progesterone group (progesterone level ≥119.45). The number of women with low pain score (less than five) in hours 12 and 24 was significantly higher in high progesterone level group. With increasing BMI, progesterone level was lower and women with higher BMI, had a higher pain score in hours 4, 8, 12, and 24, while women with lower BMI had a lower pain score during the same hours. ( p = .004, r = 0.223; p = .004, r = 0.223; p = .039, r = 0.160; and p = .007, r = 0.207). Progesterone level and BMI ( p = .025, r = − 0.174), and progesterone level and pain score in hours 4, 8, 12, and 24 ( p = .000, r = − 0.324; p = .000, r = − 0.474; p = .000, r = − 0.329; and p = .000, r = − 0.417, respectively) showed a negative significant correlation. Putting three variables of age, gestational age, and BMI in a multiple regression model, progesterone level showed significant negative correlation with the pain score in hour 4 ( p = .000, r = − 0.305), hour 8 ( p = .000, r = − 0.461), hour 12 ( p = .000, r = − 0.328), and hour 24 ( p = .000, r = − 0.409). Conclusions: Serum progesterone level showed a negative correlation with the pain score after cesarean section.